2016
DOI: 10.1111/dom.12714
|View full text |Cite
|
Sign up to set email alerts
|

Role of long non‐coding RNAs in the determination of β‐cell identity

Abstract: Pancreatic β-cells are highly specialized cells committed to secrete insulin in response to changes in the level of nutrients, hormones and neurotransmitters. Chronic exposure to elevated concentrations of glucose, fatty acids or inflammatory mediators can result in modifications in β-cell gene expression that alter their functional properties. This can lead to the release of insufficient amount of insulin to cover the organism's needs, and thus to the development of diabetes mellitus. Although most of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 137 publications
(176 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, some LncRNAs are responsive to obesity. Motterle and coworkers reported that the expression of βlinc1 and βlinc2 correlated with body weight gain and glucose levels in diabetic animals, and the expression of the human ortholog of βlinc3 in the islets of T2D patients was altered and was related to the body mass index 14 . Also, our most recent work demonstrated that lncRNA Roit expression was downregulated in the islets of obese mice, impairing the transcription of the insulin gene and glucose homeostasis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some LncRNAs are responsive to obesity. Motterle and coworkers reported that the expression of βlinc1 and βlinc2 correlated with body weight gain and glucose levels in diabetic animals, and the expression of the human ortholog of βlinc3 in the islets of T2D patients was altered and was related to the body mass index 14 . Also, our most recent work demonstrated that lncRNA Roit expression was downregulated in the islets of obese mice, impairing the transcription of the insulin gene and glucose homeostasis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) are emerging as important players in the regulation of β‐cell function . Some of these non‐coding transcripts may potentially also be released in exosomes.…”
Section: Metabolic Organs Releasing Exosomesmentioning
confidence: 92%
“…Although the role of miRNAs in diabetes has been well established (9), analyses of lncRNAs in islets have lagged behind their short ncRNA counterparts. However, several recent studies provide evidence that lncRNAs are crucial components of the islet regulome and may have a role in diabetes (27). For example, a genome-wide association study examined T2D susceptibility loci within unknown genomic associations and found that a significant percentage (>16%) of T2D loci contained islet lncRNAs within 150 kb of the reported lead single nucleotide polymorphism (SNP) (28), suggesting lncRNAs are essential for normal pancreatic function.…”
Section: Noncoding Rnasmentioning
confidence: 99%